2020
DOI: 10.1002/jcsm.12566
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity trajectories, mortality, hospitalization, and disability in the Toledo Study of Healthy Aging

Abstract: Background Physical activity (PA) is a recognized contributor to healthy aging. However, the majority of studies exploring its associations with adverse outcomes in cohorts of older adults use single‐time PA estimates, which do not consider its dynamic nature. The aim of the present study is to explore the presence of different PA trajectories in the Toledo Study of Healthy Aging and their association with adverse outcomes. Our hypothesis is that prospectively maintaining or increasing PA is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 76 publications
0
32
0
Order By: Relevance
“…Similar trajectories (always sedentary, fast declining, stable moderate, and always active) were reported in a study from the U.S. among a sample of older women aged 70–79 years, however, the authors found no increasing trajectory which was explained with the high age of the study participants [ 41 ]. Most studies describe three to four trajectories or patterns [ 19 , 26 , 41 ], and less often more are reported, as in a European study conducted in Spain with more than 1600 participants, reporting very diversified patterns (high PA—consistent, moderate PA—mildly decreasing, low PA—increasing, moderate PA—consistent, and low PA—decreasing) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar trajectories (always sedentary, fast declining, stable moderate, and always active) were reported in a study from the U.S. among a sample of older women aged 70–79 years, however, the authors found no increasing trajectory which was explained with the high age of the study participants [ 41 ]. Most studies describe three to four trajectories or patterns [ 19 , 26 , 41 ], and less often more are reported, as in a European study conducted in Spain with more than 1600 participants, reporting very diversified patterns (high PA—consistent, moderate PA—mildly decreasing, low PA—increasing, moderate PA—consistent, and low PA—decreasing) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In later life, PA can prevent cognitive decline and improve physical functioning [ 7 , 8 , 9 , 10 ]. Among the elderly, activities of daily living can longer be maintained when engaging in regular PA [ 11 , 12 ]. Finally, the beneficial effects might delay premature mortality and increase one’s lifespan [ 6 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have attempted to address this gap by considering the evolution of PA over time. [16][17][18][19][20][21][22][23][24][25] However, most of those studies were based on conventional methods to identify groups with different PA trajectories, which typically use clinical or empirical cut-points. [16][17][18][19][20][21] To reduce the reliance on these cut-points, data-driven approaches such as growth mixture modelling have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…22,28 Using this approach, studies have shown PA trajectories in older adults 29,30 were associated with multiple health outcomes including disability, cardiovascular diseases, and all-cause mortality. [22][23][24][25]31 However, the associations of PA trajectories with CP and is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Geroscience is a recent field of investigations in the broad gerontology discipline, born from the hypothesis that by manipulating biological aging it is possible to prevent or delay the onset of chronic conditions, as well as their severity ( Sierra and Kohanski, 2017 ; Sierra, 2016a , b ; Kennedy et al, 2014 ). Physical activity (PA) and exercise are considered powerful behaviors for reducing the risk of developing a myriad of chronic diseases ( de Souto Barreto et al, 2017 ; Lee et al, 2012 ; Nyberg et al, 2020 ; Moore et al, 2016 ; Kivimäki et al, 2019 ) and to slow down the age-related progression of the disabling cascade, such as frailty ( Abe et al, 2020 ), functional limitations and disability ( GBD 2017 Risk Factor Collaborators, 2018 ; Sanchez-Sanchez et al, 2020 ; Tak et al, 2013 ), and early mortality ( GBD 2017 Risk Factor Collaborators, 2018 ; Saint-Maurice et al, 2020 ). Since PA and exercise benefit so distinct diseases, such as cancer ( Moore et al, 2016 ), Alzheimer’s and related diseases ( Kivimäki et al, 2019 ), heart conditions ( Colpani et al, 2018 ), they can be seen as one of the best interventions for healthy aging from both epidemiological ( Lin et al, 2020 ) and gerosciences perspectives ( Ferrucci et al, 2016 ; Rebelo-Marques et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%